Carbon emission disclosure: A study of manufacturing companies in Indonesia 2018 – 2022 - Haryanto, Hery; Maharani, Diva (Universitas Negeri Yogyakarta, 2024)
Investigating the factors that affect the degree of disclosure of carbon emissions is the aim of this study. Leverage, company size, profitability, age, corporate social responsibility, and financial constraints. Multiple linear regression is the analysis model used in this investigation. A popular statistical technique for assessing the relationship between independent and dependent variables is multiple linear regression. The study's data, which was gathered from www.idx.co.id and the official websites of associated businesses, spans the years 2018–2022. Because the manufacturing sector is one of the biggest on the Indonesia Stock Exchange, it is the primary subject of this study. The Stata method was used to examine the data. The relationship between corporate social responsibility and corporate emission disclosure is positive; the more corporate social responsibility there is, the more corporate emission disclosure there is. The idea of mediation is applied in research with financial restrictions. The Sobel-Test is used to assess the relationship in the study model. The idea of mediation is applied in research with financial restrictions. The Sobel-Test is used to assess the relationship in the study model.Keywords: Corporate Emission Disclosure, Corporate Social Responsibility, Financing Constraint